Effect of Thickness on Structural, Morphological, and Optical Properties of Copper (Cu) Doped Zinc Selenide (ZnSe) Thin Films by Vacuum Evaporation Method (Journal of Bangladesh Academy of Sciences, 2020)
Effect of thickness on structural, optical and morphological properties of 2% copper (Cu) doped zinc selenide (ZnSe) thin films, grown onto chemically and ultrasonically cleaned glass substrate by thermal evaporation method in high vacuum (~10-6 Torr) were studied. Films of 100, 200, 300 and 400 nm thickness were prepared at 200℃ substrate temperature where annealing temperature and annealing time was fixed at 100℃ and 1 hour respectively. The X-ray diffraction (XRD) exhibited polycrystalline nature indicating the zinc-blende structure with a preferential orientation along the (111) plane of cubic phase. The grain size was found to be 19.27 nm. Dislocation density and microstrain were also found as 2.691 × 10-3 nm-2 and 1.85 × 10-3 respectively. Atomic Force Microscopy (AFM) study confirmed the growth of grains and their distribution over the entire surface of the films. All the films were characterized optically by UV-VIS-NIR spectrophotometer in the photon wavelength ranging from 300 to 1000 nm. The optical transmittance and reflectance were utilized to compute the absorption coefficient, extinction coefficient and band gap energy of the films. The calculated band gap energy was found to increase (2.99 to 3.94 ev) with varying thickness. The maximum transmittance was found to be 87.65% for the 400 nm film.Journal of Bangladesh Academy of Sciences, Vol. 43, No. 2, 159-168, 2019